El impacto de la tecnología digital en las relaciones de pareja - Minaya Barrrientos, Marco Antonio (2021)
The following study is a review article, the objective of which was to review, expose and understand the impact and consequences of excessive use of digital technology (Smartphone and social networks) in romantic relationships. The research has a scope of documentary analysis. It was explored from the notion of sociocultural studies of communication, emphasizing the contributions of David Morley, Manuel Castells; from the anthropological vision of cultural mass consumption, by Nestor García Canclini and Michel Maffesoli; Zygmunt Bauman's psychological vision in liquid love, and Erving Goffman's social vision, who, from their own theoretical visions, recognize the importance of the role of new technologies and their relationship with the human being. In this regard, the results indicate that the excessive use of virtual media has more negative than positive consequences in romantic relationships, since it causes permanent conflicts of mistrust, jealousy and increased emotional dependence, the solutions of which are dialogue or rupture definitive.